Theoretical Approaches in the Sociology of Professions - Elyesa Koytak (Journal of Economy Culture and Society)
The sociology of professions as a developing field in the last decade in Turkey does not yet have a theoretical and conceptual ground. This article aims to critically evaluate and classify the theoretical approaches developed to understand professions in the sociology literature since Durkheim and Weber. In sociology, professions have been analyzed from different perspectives that vary according to different national contexts and periods. The functionalist definition of professions which is rooted in Durkheimian-Flexnerian framework in particular has been dominant until the 1970s. The term profession is a legacy of this tradition which took as a universal model prestigious jobs such as the lawyer and physician that have designated a high status and high income in Western societiessince the 19th century. In this framework, professions are considered as sets of traits and attributes that are convenient to function as moral balance mechanisms. Alternatively, the concepts of professionalization and deprofessionalization offer to reconsider the established professions as dynamic processes rather than abstracted models. Since the 1970s, Weberian and Marxist approaches that emphasize conflict, struggle and power rather than harmony, have entered the field and fostered critical, skeptical and relational perspectives. Notions such as professional closure and monopoly, proletarianization, and field of power have become widespread in the last thirty years. In addition, as studies on different historical experiences increase, the need for a fundamental revision of the concept profession becomes indispensable.